Chinese Communist Materials at the Bureau of Investigation Archives, Taiwan - Donovan, Peter (Michigan Monographs In Chinese Studies, 2020)
During the long years of civil strife in China the Nationalist authorities amassed extensive materials on their Communist adversaries. Now stored in government institutions on Taiwan, these materials are an excellent source for the study of the Chinese Communist movement. Among them is the Bureau of Investigation Collection (BIC), which holds over 300,000 volumes of primary documents on the Chinese Communist movement. The purpose of Chinese Communist Materials is, without any attempt at comprehensive listing of the Bureau's holdings, to give scholars a representative description of the collection, to point out its implications for research, and suggest new areas for research at the Bureau in the fields of political science and history [1, 4].